Investigation of Control of Residual Stress Induced by CO2 Laser-Based Damage Mitigation of Fused Silica Optics - Chuanchao Zhang; Wei Liao; Lijuan Zhang; Yayun Ye; Jing Chen; Haijun Wang; Xiaoyu Luan; Xiaodong Yuan (Advances in Condensed Matter Physics)
A CO2 laser-based annealing technique for the mitigation of damaged sites of fused silica is studied to suppress the residual stress left on the surface. The laser annealing by a linear decrease of the CO2 laser power effectively reduces the residual stress. The residual stress of mitigated sites is characterized by polarimetry, the reduction of the maximum retardance around the mitigated sites with the exposure time of laser annealing fits a stretched exponential equation, and the maximum retardance with optimal laser annealing is reduced (36 ± 3)% compared to that without laser annealing. The residual stress regions are destructively characterized by introducing damage. The critical size of damage leading to fracture propagation for the mitigated sites without laser annealing is in the range of 120~230 μm, and the corresponding critical size of damage for the mitigated sites with laser annealing is larger than 600 μm. According to the relationship between maximum damage size and critical stress, the residual stress without laser annealing is in the range of 28–39 MPa and the residual stress with laser annealing is less than 17 MPa. These results indicate that the CO2 laser-based annealing technique has a positive effect on the control of residual stress induced by CO2 laser-based damage mitigation.